High Redox Capacity of Al‐Doped La1−xSrxMnO3−δ Perovskites for Splitting CO2 and H2O at Mn‐Enriched Surfaces. Issue 7 (14th February 2017) - Ezbiri, M.; Becattini, V.; Hoes, M.; Michalsky, R.; Steinfeld, A.
Abstract: Perovskites are attractive candidates for the solar‐driven thermochemical redox splitting of CO2 and H2 O into CO and H2 (syngas) and O2 . This work investigates the surface activity of La1− x Sr x Mn1− y Al y O3− δ (0≤ x ≤1, 0≤ y ≤1) and La0.6 Ca0.4 Mn0.6 Al0.4 O3− δ . At 1623 K and 15 mbar O2, the oxygen non‐stoichiometry of La0.2 Sr0.8 Mn0.8 Al0.2 O3− δ increases with the strontium content and reaches a maximum of δ =0.351. X‐ray photoelectron spectroscopy analysis indicates that manganese is the only redox‐active metal at the surface. All La1− x Sr x Mn1− y Al y O3− δ compositions exhibit surfaces enriched in manganese and depleted in strontium. We discuss how these compositional differences of the surface from the bulk lead to the beneficially higher reduction extents and lower strontium carbonate concentrations at the aluminum‐doped surfaces. Using first principles calculations, we validate the experimental reduction trends and elucidate the mechanism of the partial electronic charge redistribution upon perovskite reduction. Abstract : The big split‐up : Upon Al doping of lanthanum–strontium manganites, manganese enrichment and strontium depletion is observed at the perovskite surface. This is correlated with a higher redox activity and lower carbonate formation, both beneficial for CO2 ‐splitting applications.